An insect larvae inspired MXene-based jumping actuator with controllable motion powered by light. (1st December 2022) - Xu, Liangliang; Xue, Fuhua; Zheng, Haowen; Ji, Qixiao; Qiu, Changwen; Chen, Zhong; Zhao, Xu; Li, Pengyang; Hu, Ying; Peng, Qingyu; He, Xiaodong
Abstract: Many creatures in nature can carry objects to precisely jump, however, this is difficult to achieve in untethered artificial soft robots. Here, by mimicking the latching mechanism of the insect larva jumping, an untethered MXene-based soft actuator with adjustable jumping motion controlled by light is designed. The actuator prepared by the large size MXene nanosheets and polymer has an original closed rolled structure with an adhesive coating serving as a latch, which perfectly simulates the formed loop of the insect larva before jumping. Under light, due to the storage and sudden release of light-driven elastic energy caused by the latch, the actuator produces jumping motion. More importantly, by regulating irradiation angle to locally irradiate the actuator, it can generate elastic forces in different directions, realizing different jumping motions including high jump and long jump. Moreover, the actuator's ability to carry a load for high jump under light is also demonstrated. Graphical Abstract: ga1 Highlights: A light-driven MXene-based actuator with a bionic latch structure enabled energy accumulation and rapid release is developed. The actuator can realize controllable jumping motions (high jump and long jump) by regulating the light irradiation angle. The actuator's ability to carry a load (0.5 times its own weight) for high jump under light irradiation is also demonstrated.